A pilot study on Pedsql™ modul impak keluarga among caregivers of children with transfusion dependant thalassaemia in Hospital USM, Malaysia - Tan, Suria Emilia Suhana Othman (2013)
Thalassaemia is one of the commonest genetic blood disorders worldwide (Cao et al., v v Approximately 240 million people are heterozygous for [3-thalassaemia and estimated 200.000 affected homozygous are born each year(Cao et al., 2007). In Malaysia, it was estimated that around 150 to 350 babies were born with thalassaemia each year (Ismail et al., 2006). A child with beta thalassemia usually is well at birth, but they will develop progressive anemia due to partial or total absence in hemoglobin, which will lead to early death without blood transfusion. In those who survive, the condition imposes serious implications on their health and quality of life as well as their families. Parents of children with transfusion dependant thalassaemia need to accompany their child for monthly blood transfusion in which they usually spend the whole day in the hospital. The children need to come in the morning for blood investigations to check for hemoglobin level and blood cross match and then, they need to wait for the blood products to be available. Usually, this process takes about two to three hours but it may be prolonged if there is a problem with the children's blood. For example, if the children develop autoantibodies towards the red blood cell, the blood bank needs to do further test to find the most suitable blood for the child. It may take another one or two days depending on the availability of blood and severity of the autoantibodies. Thus, the parents need to bring the child home first and then bring back the child to the hospital once the blood is ready. For the uncomplicated situation, the children need to wait for two to three hours for blood cross matching and then only the blood transfusion can be started. The duration for each transfusion usually takes about 4 hours. The children also need frequent iron chelation therapy in order to reduce the impact of transfusion-related toxicity due to iron overload. This iron chelation therapy is available in subcutaneous and oral form. Unfortunately, this therapy also has its own adverse effects and limitations that contribute to noncompliance to the drugs. Patient who does not comply to iron chelation therapy often develop various complications such as cardiomyopathy, endocrinopathy, infection, coagulopathy, liver toxicity and others that might compromising the child and family quality of life further. Currently, only successful hematopoietic stem cell transplant (HSCT) can offer a permanent cure but it is limited by HLA-matched sibling donor and procedure related complication (Cheuk et al., 2008). Thus, parents of these children are exposed to protracted physical and emotional suffering because of their children’s devastating health problem leading to disruption of their normal psychosocial life. Previous literature has mainly focused on assessing health-related quality of life in children with beta thalassaemia but less is known about their parents and families (Ismail et al., 2006; Dahlui et al., 2009; Clarke et al., 2010). Findings of studies conducted elsewhere might not be the reflection of true Malaysian due to difference in their ethnicity, religion and socioeconomic background of the family. Therefore, this study was conducted to look at the impact of having a child with beta thalassaemia on the parents’ health-related quality of life (HRQOL) and family functioning in Kelantan.